Current Trends in Interprofessional Education of Health Sciences Students: A Literature Review - Abu-Rish, Erin L. (J Interprof Care, 2012)
There is a pressing need to redesign health professions education and integrate an interprofessional and systems approach into training. At the core of interprofessional education is creating training synergies across healthcare professions and equipping learners with the collaborative skills required for today’s complex health care environment. Educators are increasingly experimenting with new interprofessional education (IPE) models, but best practices for translating IPE into interprofessional practice (IPP) and team-based care are not well defined. Our study explores current IPE models to identify emerging trends in strategies reported in published studies. We report key characteristics of 83 studies that report IPE activities between 2005 and 2010, including those utilizing qualitative, quantitative, and mixed method research approaches. We found a wide array of IPE models and educational components. Although most studies reported outcomes in student learning about professional roles, team communication, and general satisfaction with IPE activities, our review identified inconsistencies and shortcomings in how IPE activities are conceptualized, implemented, assessed, and reported. Clearer specifications of minimal reporting requirements are useful for developing and testing IPE models that can inform and facilitate successful translation of IPE best practices into academic and clinical practice arenas.